Influence of mechanochemical technology on anthelmintic efficacy of the supramolecular complex of fenbendazole with polyvinylpyrrolidone - Arkhipov, Ivan A; Khalikov, Salavat S; Sadov, Konstantin M; Dushkin, Alexander V; Meteleva, Elizaveta S; Varlamova, Anastasiya I; Odoevskaya, Irina M; Danilevskaya, Nataliya V (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The purpose of our research was to evaluate the effect of mechanochemical technology on the efficacy of supramolecular complex of fenbendazole (SMCF) with polyvinylpyrrolidone (PVP) polymer against some helminthosis of animals. Materials and Methods: The SMCF samples with PVP were synthesized using a solid-state mechanochemical technology in activators of impact-abrading type and their physicochemical properties were analyzed. The efficacy of SMCF was studied on the laboratory model of Hymenolepis nana and Trichinella spiralis infection of mice and helminthosis of sheep. Results: In the trials conducted on laboratory models, the supramolecular complex showed 93.94% and 98.56 % efficacy at the dose of 1 mg/kg of body weight (b/w), while the substance of fenbendazole showed 7.97% and 8.33% efficacy at the same dose. A high efficacy (>94%) of the SMCF was revealed at the dose of 2.0 mg/kg of b/w at oral administration against nematodes in naturally infected sheep by the results of the fecal examination, while the substance of fenbendazole was active at the dose of 5.0 mg/kg at single oral administration. Moreover, the SMCF demonstrated 97.37% efficacy at the dose of 2 mg/kg against Moniezia spp. infection of sheep. Physicochemical studies confirmed the increase in solubility of the complex, reducing of particle sizes, amorphization of fenbendazole substance, and incorporating it with micelles of PVP. Conclusion: According to the results, supramolecular complex of fenbendazole with PVP was more active than the basic substance of fenbendazole and its anthelmintic properties were expanded. J. Adv. Vet. Anim. Res., 6(1): 133-141, March 2019